ANALYSIS KEJADIAN FRAUD PADA SEBUAH FINTECH - Andre Pratama Adiwijaya (Asosiasi Dosen Muda Indonesia, 2024)
Fraud detection in technology-based financial services (Fintech) is one of the main challenges in the digital era. This research aims to develop a productive fraud detection system using data analytics and machine learning techniques. This project utilizes Python for algorithm implementation, accompanied by process visualization through flowcharts and analysis of related datasets. The resulting system is expected to be able to improve accuracy in detecting suspicious activities.